Faktor Faktor yang Memengaruhi Pendapatan Asli Daerah (PAD) Kabupaten/Kota di Provinsi Jawa Timur tahun 2023-2025 - Eka Febrianti; Puji Astuti; Faisol Faisol (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
Regional Original Revenue (PAD) is an important indicator in reflecting the level of regional fiscal independence to support the implementation of regional autonomy and sustainable development. A high level of PAD indicates the ability of local governments to finance development needs independently without excessive dependence on the central government. This study aims to analyze the effect of local taxes, regional retributions, capital expenditure, and Gross Regional Domestic Product (GRDP) on Regional Original Revenue in regencies and municipalities in East Java during 2023–2025. This study employed a quantitative approach using panel data analysis by combining cross-section and time-series data. The sample consisted of all regencies and municipalities in East Java selected through a non-probability sampling  technique using a census or total sampling  method. The data were obtained from official government publications and analyzed using panel data regression with the assistance of STATA software. The results indicate that partially and simultaneously local taxes, regional retributions, capital expenditure, and GRDP have a positive and significant effect on Regional Original Revenue. Local taxes and regional retributions contribute to increasing regional revenue through the optimization of local revenue sources, while capital expenditure encourages infrastructure development and improves public services that support regional economic activities. Furthermore, increasing GRDP reflects regional economic growth that expands the regional revenue base. These findings imply that local governments need to optimize fiscal policies, improve public service quality, strengthen regional economic productivity, and allocate capital expenditure effectively to enhance regional revenue and fiscal independence.